The Impact of Teaching Mathematics Using Advanced Organizer Strategy on the Achievement and Development of Reflective Thinking Skills Among Tenth Grade Students in Jordan - Al-Halalmeh, Maysam Salama Hassan; Abu Sneina, Odeh AbdelGawad (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to identify the effect of teaching mathematics according to strategy of the advanced organizer on achievement and reflective thinking skills in the mathematics subject for tenth-grade students. To achieve the study’s goal, the researcher prepared a special educational program that employs the strategy of the advanced organizer in classroom situations, and an achievement test. The researcher also applied the reflective thinking test to measure reflective thinking skills. The researcher applied the strategy of the advanced organizer to the tenth-grade students in the tenth grade in Baraem Al Rabeeh School and Kindergarten in the Capital Governorate Amman in Jordan. 20 male and female students, and an experimental group of (20) male and female students. The results of the study showed that the use of the advanced organizer strategy had an impact on improving the achievement level of the tenth grade students in mathematics, and that the use of the advanced organizer strategy had an effect on the reflective thinking skills of tenth- grade students in the mathematics subject, The study made several recommendations, the most important of which are: The necessity for mathematics teachers in the different educational stages to adopt the strategy of the advanced organizer in planning and implementing their lessons.